Attitudes toward Same-Sex Attraction and Behavior among Chinese University Students: Tendencies, Correlates, and Gender Differences - Chi, Xinli; Hawk, Skyler T. (Frontiers in Psychology, 2016)
The present study examined Chinese university students’ attitudes toward same-sex attraction and behavior, the socio-demographic correlates of these attitudes, and the potential gender differences in both tendencies and correlates. A total of 2,644 Chinese university students (49.7% male, mean age = 20.27 years) indicated generally negative attitudes toward same-sex attraction and behavior, with males reporting more negative attitudes than females. More years in university (i.e., higher grade levels), higher levels of maternal education, growing up in an urban area, and more frequent Internet use significantly predicted more positive attitudes. Gender significantly moderated one correlate: For female participants, a higher university grade was related to more positive attitudes; this correlation was not significant for male participants. The findings suggest valuable directions for related intervention practices for young people in China. Key words: Chinese university students, same-sex attraction and behavior, gender differences